Analogie ed Equivoci nel dialogo fra architetti e musicisti. Gli esiti di una tavola rotonda (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2019)
This commentary collects the most significant topics from a round table held in 2012 during the Conference on ‘Music and Architecture’ with contributes by Stefano Catucci, Maurizio Gabrieli, Giorgio Muratore, Franco Purini, Giani Trovalusci. The topics are sinthetised under two major cathegories: analogies and misunderstandings.